2020
DOI: 10.1002/apj.2514
|View full text |Cite
|
Sign up to set email alerts
|

Influence of temperature dependent viscosity and internal heating on the onset of convection in porous enclosures saturated with viscoelastic fluid

Abstract: The combined influence of temperature dependent viscosity and internal heat source on the onset of convection in porous enclosures saturated by a viscoelastic fluid is studied using linear and weak nonlinear stability theories. The enclosures are taken to be rectangular, square, and slender. For the viscoelastic fluid, the Oldroyd-B type model is used, whereas the Darcy's model is taken for porous medium. The linear theory based on normal mode technique is used to find the criteria for the onset of marginal an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 61 publications
0
11
0
Order By: Relevance
“…Research on viscoelastic liquids is done by various researchers. [13][14][15][16][17][18][19][20][21][22][23][24] Kayodé and Khayat 25 compared the solutions of Newtonian and non-Newtonian liquids and it was noted that the effect of elasticity in the liquid is found to be greater for higher Rayleigh numbers. Siddheshwar et al 26 concluded that the Maxwell liquids are comparatively more stable than other liquids in the study.…”
mentioning
confidence: 99%
“…Research on viscoelastic liquids is done by various researchers. [13][14][15][16][17][18][19][20][21][22][23][24] Kayodé and Khayat 25 compared the solutions of Newtonian and non-Newtonian liquids and it was noted that the effect of elasticity in the liquid is found to be greater for higher Rayleigh numbers. Siddheshwar et al 26 concluded that the Maxwell liquids are comparatively more stable than other liquids in the study.…”
mentioning
confidence: 99%
“…We now turn to the very small perturbations on the basic flow. Therefore, after small perturbations, the variables acquire the form as 38–41 boldv=vb+ε1v,1emθ=θb+ε1θ,1emP=Pb+ε1P.…”
Section: Perturbed Equationsmentioning
confidence: 99%
“…where primes indicate the perturbed quantities. Equation ( 10) is substituted back into Equations ( 5) to (8), and the pressure term is eliminated from the momentum equation by operating curl and a perturbation stream function ψ x z t ′( , , ) with…”
Section: Smmentioning
confidence: 99%
“…The thermal instability in a horizontal layer of a couple stress nanofluid in a porous medium is investigated by Chand et al 6 Yadav and Wang 7 analyzed the effect of temperature‐dependent internal heat source on the onset of convection and on the heat transfer in a porous layer saturated by a non‐Newtonian nanofluid. The combined influence of temperature‐dependent viscosity and internal heat source on the onset of convection in porous enclosures saturated by a viscoelastic fluid is studied by Yadav and Maqhusi 8 . Besides, double‐diffusive convection in a layer of couple stress fluid saturating a porous medium has also been investigated 9‐17 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation